(3GdgLQI ZjQ GdTQYjI aj Ohd ZQHj GdeJhSW (B:s (3OQGSI GdJLeY GdEbdjej (B(5 + 5) /s - (3GdhQadj, hfjSI GdMeQhfjs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2016)
(3SYJ gPg GdOQGSI dJhVjM eaghe GdgLQI ZjQ GdTQYjI heYQaI CSHGHgG hCHYGOgG hJCKjQgG Ydi GdYdGbGJ Hjf Ohd ZQHj GdeJhSW HGYJHGQgG XGgQI ef Cge GdXhGgQ GdHGQRI hGdJj GQJHWJ HGdEfSGf efP XghQg Ydi hLg GdCQV hUfaJ Cj GdgLQI ZjQ GdTQYjI Ydi CfgG XGgQI YGdejI JJeKd aj GfJbGd GdCaQGO ef ecGf Edi BNQ HMKG Yf MjGI CaVd Ch gQhHG ef hVY eYjf HTcd ZjQ eTQhY(B.s
(3HHdjhLQGajI (B: (3UaMI (B263-271.s
Keywords: (3GdgLQI ZjQ GdTQYjIs -- (3MhV GdHMQ GdCHjV GdeJhSWs; (3GdGZJQGH GdGLJeGYjs -- (3MhV GdHMQ GdCHjV GdeJhSWs; (3GdgLQIs -- (3LhGfH GLJeGYjIs -- (3MhV GdHMQ GdCHjV GdeJhSWs